2018
DOI: 10.1016/j.jcjd.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Natural Clinoptilolite and Nano-Sized Clinoptilolite Supplementation on Glucose Levels and Oxidative Stress in Rats With Type 1 Diabetes

Abstract: Nano-sized clinoptilolite exerted a hypoglycemic effect in streptozotocin-induced diabetic rats but had no significant influence on oxidative stress markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Zeolite was used in our study for the following reasons: zeolite is capable of adsorbing many different types of gas, moisture, petrochemicals, heavy metals and radioactive elements and a multitude of various compounds; it has a total cation-exchange capacity of about 200 mEq. The exchange capacity plays an important role in the therapeutic use of zeolite, accounting for its ability to release useful elements while capturing and binding others [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zeolite was used in our study for the following reasons: zeolite is capable of adsorbing many different types of gas, moisture, petrochemicals, heavy metals and radioactive elements and a multitude of various compounds; it has a total cation-exchange capacity of about 200 mEq. The exchange capacity plays an important role in the therapeutic use of zeolite, accounting for its ability to release useful elements while capturing and binding others [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although natural nanosized clinoptilolite and/or metformin did not affect pronouncedly the levels of serum glucose, minerals, and lipid profile in rats with high-fat-diet/STZ induced diabetes, the co-treatment of clinoptilolite with the drug notably increased high-density lipoprotein (HDL) cholesterol, while Cu and Ca levels increased only in the metformin group [201]. In STZ induced diabetic rats treated with nanosized clinoptilolite, blood glucose was found to decrease to near normal levels (12.4 vs. 27.5 mmol/L), but no significant impact on oxidative stress markers was estimated [202]. Nanosized clinoptilolite injected to STZ induced diabetic rats caused a partial improvement in their weight status and lack of undesirable effects, although beneficial changes in lipid profile were not detected, which could be connected with short study duration [203].…”
Section: Other Functional Applications Of Human Supplementsmentioning
confidence: 99%
“…Several studies have been conducted on using the cold plasma in diabetes mellitus complications treatment, directly, such as wound healing in case of diabetic rats, and indirectly such as nano-sized clinoptilolite production by the cold plasma, and its effect on reducing hyperglycemia in rats 2,5,23 . Also, in recently promising study has been reported after diabetic wound treatment by the cold plasma, the levels of superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT) elevated, and the result of CAP on wound healing revealed the plasma role in upregulating cytokines secretion (as an important part of inflammatory system) such as IL-1, and IL-6 5,24 .…”
Section: Introductionmentioning
confidence: 99%